2017
DOI: 10.1039/c7ta01947e
|View full text |Cite
|
Sign up to set email alerts
|

High-performance, ultra-flexible and transparent embedded metallic mesh electrodes by selective electrodeposition for all-solid-state supercapacitor applications

Abstract: High-performance, ultra-flexible and transparent embedded metallic mesh electrodes were fabricatedvialow-cost selective electrodeposition process combined with inverted film-processing methods for the first time. Flexible and transparent all-solid-state supercapacitors were thus successfully constructed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 49 publications
0
58
0
Order By: Relevance
“…There is a wide variety of conductive polymers such as polyacetylene, 7 polypyrrole, 8 polythiophene, and poly(3,4-ethylene dioxythiophene):poly(styrene sulfonate) (PEDOT:PSS). 9 Among these, PEDOT:PSS exhibits the best electrical and optical properties [10][11][12][13][14] and is utilized in organic electronic devices such as organic light emitting diodes (OLEDs) 15 and organic photovoltaics (OPVs). 16 Therefore, it is considered as a potential organic electronic material.…”
Section: Introductionmentioning
confidence: 99%
“…There is a wide variety of conductive polymers such as polyacetylene, 7 polypyrrole, 8 polythiophene, and poly(3,4-ethylene dioxythiophene):poly(styrene sulfonate) (PEDOT:PSS). 9 Among these, PEDOT:PSS exhibits the best electrical and optical properties [10][11][12][13][14] and is utilized in organic electronic devices such as organic light emitting diodes (OLEDs) 15 and organic photovoltaics (OPVs). 16 Therefore, it is considered as a potential organic electronic material.…”
Section: Introductionmentioning
confidence: 99%
“…[54][55][56][57][58][59][60][61] For example, by integrating into a Ni mesh, PEDOT : PSS-based TESE realizes an extremely high FoM e of 10000 at high transparency of 84 %. [62] More importantly, Coleman and his teammates found that no percolation issue is confronted for PEDOT : PSS films even at high transparency of 99 %, showing the great promise of PEDOT : PSS-based TESEs. Of noticeable shortcoming is the low FoM c for most of the reported polymers-based TESEs due to the low areal capacitance.…”
Section: Batteries and Supercapsmentioning
confidence: 99%
“…Several approaches on the realization of TCEs were reported, including nanoimprinting, [ 139 ] photolithography, [ 140 ] wet etching, [ 141 ] laser direct writing lithography, [ 111,135,142,143 ] and direct printing technique. [ 136,137,144 ] Xu et al [ 111 ] fabricated the embedded Ag‐grid TCE as a current collector for flexible transparent SCs.…”
Section: Transparent Conductive Electrodesmentioning
confidence: 99%